Bee venom processes human skin lipids for presentation by CD1a. - Bourgeois, E; Subramaniam, S; Cheng, T; De Jong, A; Layre, E; Ly, D; Salimi, M; Legaspi, A; Modlin, R; Salio, M; Cerundolo, V; Moody, D; et al. (Rockefeller University Press, 2015)
Venoms frequently co-opt host immune responses, so study of their mode of action can provide insight into novel inflammatory pathways. Using bee and wasp venom responses as a model system, we investigated whether venoms contain CD1-presented antigens. Here, we show that venoms activate human T cells via CD1a proteins. Whereas CD1 proteins typically present lipids, chromatographic separation of venoms unexpectedly showed that stimulatory factors partition into protein-containing fractions. This finding was explained by demonstrating that bee venom–derived phospholipase A2 (PLA2) activates T cells through generation of small neoantigens, such as free fatty acids and lysophospholipids, from common phosphodiacylglycerides. Patient studies showed that injected PLA2 generates lysophospholipids within human skin in vivo, and polyclonal T cell responses are dependent on CD1a protein and PLA2. These findings support a previously unknown skin immune response based on T cell recognition of CD1a proteins and lipid neoantigen generated in vivo by phospholipases. The findings have implications for skin barrier sensing by T cells and mechanisms underlying phospholipase-dependent inflammatory skin disease.